Preterm birth clinical risk factors and prevention - Illescas Castañeda, José Alfredo (2015)
We must consider preterm birth when occurring at 22 through 34 weeks gestation as perinatal morbidity and mortality is not clinically significant from 34 weeks on. Notwithstanding advances in medical knowledge and technology, worldwide preterm births’ incidence remains invariable. Known risk conditions like infections, preeclampsia, congenital malformations and cervical incompetence are associated in only 40 to 50% of the cases; in the rest of patients etiology remains unknown. Prenatal control and community prevention intents have not had expected results. Cervical length by ultrasound is important for risk patients’ screening and is more rapid and economic than fetal fibronectin detection in cervicovaginal secretion. At Instituto Nacional Materno Perinatal a differentiated area has been implemented for treating these patients. Considering all therapeutic agents used only micronized progesterone has shown clinical usefulness in prophylaxis and in regards to tocolytics only atosiban and nifedipine are effective and have less collateral effects.